Dielectric and electrical characteristics of palm oil-based nanofluid as high voltage insulation material / Mohamad Zul Hilmey Makmud - Mohamad Zul Hilmey , Makmud (2019)
High voltage (HV) transformer is one of the most important apparatus in power industries. With an increase of power demand, the rated power of a HV transformer is also increasing rapidly. Hence, the need to provide insulation material for a transformer without any risk of failure is essential. Nowadays, nanofluid is one of the insulation materials most widely studied. Although many researches have been done on nanofluid breakdown strength in the past, there is still lack of work on the influence of nanoparticle types and concentrations on dielectric characteristics of palm oil-based nanofluids as HV insulation in coming future. Therefore, in this work, investigation on the effects of conductive and semiconductive nanoparticles towards dielectric responses of palm oil-based nanofluids has been conducted. Iron (II,III) oxide, Fe3O4 (conductive) and Titanium dioxide, TiO2 (semiconductive) are utilized as the nanoparticle due to their capabilities to trap electrons and have higher dissolution rate in a neutral suspension. The responses of electrical characteristics such as; dielectric properties, current-voltage (I-V) curves, partial discharge (PD) activities and breakdown voltage (BDV) were measured from base oil and six types of nanofluid samples. A stability analysis was also performed to investigate the influence of nanoparticles and their amount of concentrations on dispersion characteristics of nanofluid insulation. As overall, the findings from this research indicate that palm oil with conductive nanoparticles at a very low amount of concentration (in this work, 0.01 g/L) is the most effective nanofluid insulation. In terms of reliability, palm oil with semiconductive nanoparticles is more practical as insulating material due to its aggregation stability and consistency as electrons trap although in higher amount of particle concentration (in this case, 1.0 g/L).